Talin B is required for force transmission in morphogenesis of Dictyostelium - Tsujioka, Masatsune (2004)
Talin plays a key role in the assembly and stabilisation of focal adhesions, but whether it is directly involved in force transmission during morphogenesis remains to be elucidated. We show that the traction force of Dictyostelium cells mutant for one of its two talin genes talB is considerably smaller than that of wild-type cells, both in isolation and within tissues undergoing morphogenetic movement. The motility of mutant cells in tightly packed tissues in vivo or under strong resistance conditions in vitro was lower than that of wild-type cells, but their motility under low external force conditions was not impaired, indicating inefficient transmission of force in mutant cells. Antibody staining revealed that the talB gene product (talin B) exists as small units subjacent to the cell membrane at adhesion sites without forming large focal adhesion-like assemblies. The total amount of talin B on the cell membrane was larger in prestalk cells, which exert larger force than prespore cells during morphogenesis. We conclude that talin B is involved in force transmission between the cytoskeleton and cell exterior.